Paradox in Melanie Martinez’s Song Lyrics, “Lunchbox Friends and Fire Drill” - Rita Napitupulu; Stefany Kangginata (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
This research, done is to explore about the paradox used in the song lyrics, and through the exploration will be known how and why it is used there. The research conducted by using the method of qualitative research, which does not use statistical data; it is collected in the form of written, spoken, or observed behavior. The researcher also uses the library research in the collecting data. Findings of this research are paradox is used by bringing order to the ambiguous shared meanings that are provided by perceptions of reality, constructing a draft to use as a guide for their future research, reformulating element of modern, industrial society, understanding the start or result of research, supporting the suitability of the goal of the research, giving space to have critical quality, amplify contrast between elements of the lyrics. Through this research is hoped that it can inspire the readers to deeper into the subject of paradox, spark the discussion of the paradox sentences or ideas in Martinez’s lyrics, so that the readers can have a better understanding about the paradox itself.